PERANCANGAN SISTEM INFORMASI PENCATATAN PEMBAYARAN SPP PADA PONDOK PESANTREN MODERN TGK CHIEK OEMAR DIYAN - Ubbaidillah, Ubbaidillah; Evayani, Evayani (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2020)
The development of technology today is very rapid and many innovations created such as administrative information systems have been used by many parties, both organizations and educational institutions. Especially in pesantren educational institutions that still use manual administrative information systems, therefore this study aims to assist the Administration in matters relating to the SPP payment process and SPP payment reports that are efficient and effective using desktops. This application is made with Xampp software and uses the PHP programming language that uses the System Development Life Cycle (SDLC) method. The results of the study were desktop-based SPP payment applications at the Tgk Chiek Oemar Diyan Modern Islamic Boarding School